2022
DOI: 10.3390/nu14061299
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Left Ventricular Performance in Patients with Different Glycometabolic Phenotypes

Abstract: The aim of the present study was to evaluate the possible correlation between oxidative stress and subclinical myocardial damage, assessed with speckle tracking echocardiography (STE), in normal glucose tolerance (NGT) patients with one-hour plasma glucose values ≥ 155 mg/dL (NGT ≥ 155), comparing them to NGT < 155 subjects, impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM) newly diagnosed patients. We enrolled 100 Caucasian patients. All subjects underwent OGTT. The serum values of oxida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Notably, RHI and PWV follow-up values were comparable to those of newly diagnosed hypertensive patients without diabetes or CV complications ( Sciacqua et al, 2012 ; Cassano et al, 2021 ). Similarly, the indicators of inflammation, in particular hs-CRP, and of oxidative stress significantly improved with Sacubitril/Valsartan to such an extent that they were comparable to those of normotolerant hypertensive patients ( Cassano et al, 2022 ) ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Notably, RHI and PWV follow-up values were comparable to those of newly diagnosed hypertensive patients without diabetes or CV complications ( Sciacqua et al, 2012 ; Cassano et al, 2021 ). Similarly, the indicators of inflammation, in particular hs-CRP, and of oxidative stress significantly improved with Sacubitril/Valsartan to such an extent that they were comparable to those of normotolerant hypertensive patients ( Cassano et al, 2022 ) ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, our results demonstrated a significant improvement in metabolically in-dices such as FPG, FPI, HbA1c and HOMA, and these data are in agreement with our previous evidence ( Armentaro et al, 2022 ). Many studies demonstrated that hyperglycemia triggers vascular damage by creating imbalance between NO availability and ROS accumulation ( Kaur et al, 2018 ; Cassano et al, 2022 ). Moreover, chronic hyperglycaemia injures vascular wall by many cellular mechanisms, including an increased production of intracellular advanced glycation end products (AGEs), raised expression of AGE receptors (RAGE) and ligands, activation of protein kinase C (PKC), augmented polyol and hexosamine flux and over activation of the hexosamine pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Notably, we recently demonstrated that NGT≥155 exhibit premature functional impairment of myocardial contractile fibre assessed by speckle tracking echocardiography (STE) and increased oxidative stress biomarkers in comparison with NGT < 155, with values similar to IGT patients. 5 All these observations emphasise the correlation between precocious variation of glucose tolerance and subclinical myocardial damage.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, our previous studies have shown that coronary flow reserve (CFR), a marker of coronary microcirculation, as well as LV myocardial strain, is impaired in first-degree relatives (FDR) of diabetic patients and dysglycaemic subjects compared with normoglycaemic subjects [ 10 , 11 ]. A recent study revealed that subjects with normal glucose tolerance with one-hour glucose levels ≥ 155 mg/dL during an oral glucose tolerance test (OGTT) had subclinical impairment in LV myocardial performance, and this finding was correlated with increased oxidative stress [ 12 ]. However, little is known about the association of endothelial glycocalyx, coronary microcirculation and LV myocardial function with the kinetics of oxidative stress markers and nitrite/nitrate levels during postprandial hyperglycaemia.…”
Section: Introductionmentioning
confidence: 99%